Analisis Pengaruh ChatGPT Terhadap Tingkat Kemalasan Berpikir Mahasiswa ITS Dalam Proses Pengerjaan Tugas - Alya Resti Saraswati; Vasya Ayu Karmina; Maharani Putri Efendi; Zahrina Candrakanti; Nur Aini Rakhmawati (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
In the continuously evolving digital era, Information and Communication Technology (ICT) has transformed the landscape of higher education. One of the emerging innovations is the use of ChatGPT. The use of ChatGPT in the learning process can also have complex impacts. One of the aspects that needs attention is the possibility of an increase in students' levels of laziness, as ChatGPT can interpret and engage in natural human language conversations. The objective of this research is to provide an understanding of how the use of ChatGPT in the context of higher education can influence student behavior and motivation. The research conducted is of an analytical observational type with a cross-sectional approach. The research was conducted at the Institut Teknologi Sepuluh Nopember in Surabaya. The population in this study consisted of ITS students. The sample used in this research included 100 ITS students. Data collection techniques in this study involved surveys through Google Forms and observations. The instruments used in the research included validity sheets, observation sheets, and documentation. Data analysis techniques used in this research included validity testing, observation data analysis, prerequisite testing, and hypothesis testing. The research results indicate that there is an influence of ChatGPT on the level of laziness among students in completing assignments. However, this influence is not statistically significant.